Synthesis of High Performance Titania (TiO2) Photocatalyst using Microwave Assisted Synthesis(MAS) Method. - Bedurus, Edmand Andrew (Journal of Science and Technology, 2014)
In the present research, Microwave Assisted Synthesis(MAS) method is applied to synthesize high performance titania(TiO2) at 150oC with various heating time. Each prepared titania are characterized by SEM, XRD and N2 sorption analysis(BET and BJH calculation). This study has shown that the prepared titania by MAS method heated at 150oC with 4 hours treatment has the highest photocatalytic performance compared to the commercial TiO2 and others titania described in this paper. The titania has effectively reduced Rhodamine B dye up to 96.72% within 90 minutes. This might be due to several factors that improved the catalytic properties of the titania such as high crystallinity of analtase crystalline phase, small crystallite size and high pore volume.